Exploration Of Humanist Values In Classical and Contemporary Indonesia Novels - Mas'ud Muhammadiah (PT. Anagata Sembagi Education, 2024)
This research seeks to uncover the essence of humanist values embedded in two notable Indonesian literary works, Siti Nurbaya by Marah Rusli and Perahu Kertas by Dee Lestari, employing a hermeneutic framework. The investigation centers on four fundamental aspects of humanism: the pursuit of justice and resistance to oppression, expressions of love intertwined with sacrifice, the journey toward self-discovery and individual autonomy, and the bonds of solidarity and friendship. The hermeneutic method was selected for its capacity to provide profound interpretative insights, enabling a nuanced understanding of the texts while integrating their broader social and cultural underpinnings. The study reveals that Siti Nurbaya emphasizes themes of defiance against social inequities and patriarchal dominance, encapsulating the socio-political realities of the colonial period. Love and sacrifice in this novel are intricately woven into the fabric of profound social struggles. Conversely, Perahu Kertas offers a contemporary lens on the quest for self-identity and personal liberty, underscored by themes of solidarity and friendship that reflect the evolving dynamics of modern social interactions. Together, these works illustrate the shifting manifestation of humanist values in response to Indonesia's changing socio-cultural and historical landscapes. This research underscores the role of literature as a powerful vehicle for introspection and social commentary, capturing the complexities of human experiences. The insights gained from this study open avenues for deeper investigations into other literary works, offering opportunities to further expand the discourse on humanist values within the rich tapestry of Indonesian literary traditions.